Peripartum Cardiomyopathy: A Review - Arzoo, Shabera; Akter, Musammat Shamima; Akther, Maher; Jannat, Fatematul (Eastern Medical College Journal, 2023)
Peripartum cardiomyopathy (PPCM) is a rare, idiopathic, and often dilated cardiomyopathy that is marked by systolic dysfunction that presents in late pregnancy or the early postpartum period. A workshop convened by the US National Heart, Lung, and Blood Institute (NHLBI) in the 1990s defined PPCM as heart failure that develops in the last month of pregnancy or up to five months postpartum with left ventricular systolic dysfunction. Prior to the availability of echocardiography, diagnosis was based only on clinical findings. Recently, the inclusion of echocardiography has made diagnosis of PPCM easier and more accurate. Etiopathogenesis is still poorly understood, but recent evidence supports inflammation, viral infection, and autoimmunity as the leading causative hypotheses. Eastern Med Coll J. July 2023; 8 (2):68-74